2011
DOI: 10.4028/www.scientific.net/amr.201-203.2875
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Oolong Tea Polyphenol and Black Tea Polyphenol on Gelatin Gels Texture

Abstract: The effects of Oolong Tea Polyphenol and Black Tea Polyphenol on Gelatin Gels Texture properties were investigated in this paper. The results showed that the brittleness and hardness of gels added black tea polyphenol was higher than that of the blank sample, however, the brittleness and hardness of gels added oolong tea polyphenol was lower than that of the blank sample. The gel elasticity was maximum when adding black tea polyphenol concentration was 2.2%(w/v), and almost no-change before or after the maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…To date, several NPs have been proposed as DNMT inhibitors [34,35]. Some studies have shown epigallocathechin-3-gallate (EGCG) [36], curcumin [34], genistein [37], psammaplin A [38], mahanine [39], caffeic acid [40], laccaic acid [41], among others. However, they exhibit no significant inhibitory pharmacological activity.…”
Section: Figure 1 May Go Herementioning
confidence: 98%
“…To date, several NPs have been proposed as DNMT inhibitors [34,35]. Some studies have shown epigallocathechin-3-gallate (EGCG) [36], curcumin [34], genistein [37], psammaplin A [38], mahanine [39], caffeic acid [40], laccaic acid [41], among others. However, they exhibit no significant inhibitory pharmacological activity.…”
Section: Figure 1 May Go Herementioning
confidence: 98%
“…Furthermore, the style and image of Sexy Tea displayed on various social media platforms give customers a unique sense of close friend, attracting a large number of fans [16]. Despite that, Sexy Tea has a very smart strategy in that it did not only focus on its brand, it cooperated with its competitor HEYTEA and launched 300 sets of co-branded gift boxes on July 21, 2020, raising a lot of fame [17]. In October of the same year, Sexy Tea and Saturnbird, a new Internet celebrity coffee brand also born in Changsha, jointly opened a store and made their co-branded products, which is also an effective approach to attract local Changsha people.…”
Section: Strengthmentioning
confidence: 99%
“…Researchers have begun conducting more studies on the physical properties of tea recently. Some studies have focused on the effects of adding tea powder or tea extracts on the physical and chemical properties of food (Wang et al, 2011;Wang, Zhou, & Isabelle, 2007;Wang, Zhou, Yu, & Chow, 2006;Yang et al, 2017;Zhu, Sakulnak, & Wang, 2016), while other studies have focused on the classification of manufactured tea (Bakhshipour, Sanaeifar, Payman, & de la Guardia, 2018;Borah, Hines, & Bhuyan, 2006;Gill, Kumar, & Agarwal, 2013;Laddi, Sharma, Kumar, & Kapur, 2013;Wu, Chen, & He, 2009) and adjustment of the processing parameters (Tang, Su, et al, 2015), monitoring the tea leaves during processing (Borah & Bhuyan, 2005), and classification of the made tea (Borah et al, 2006;Gill, Kumar, & Agarwal, 2011;Laddi et al, 2013;Zhu, Ye, He, & Dong, 2017) based on computer vision technology and image texture analysis.…”
mentioning
confidence: 99%